VD_FINDINFO AI 433/07 - 397/2011 vom 15. August 2011 - VD Tribunal cantonal (2011)
RENTE D'INVALIDITÉ, EXPERTISE PSYCHIATRIQUE, ÉVALUATION DE L'INVALIDITÉ | 29 al. 1 let. b LAI, 4 al. 1 LAI, 6 LPGA, 7 LPGA, 8 al. 1 LPGA